Relationship of Mother’s Characteristics and Nutritional Status in Children in Indonesia - Jeviya Marsianah; Rosihan Adhani; Adi Nugroho; Husaini Husaini; Bahrul Ilmi (Lambung Mangkurat, 2022)
Nutrition plays an important role in the human life cycle from in the womb to old age. The 2009 health law states that the main priority of efforts to improve nutrition in Indonesia is vulnerable groups, one of which is infants and toddlers. The results of the study used the Evidence Gap theory with the aim of analyzing the relationship between maternal characteristics and malnutrition status in children under five in Indonesia based on published studies from 2015-2020. The research method is meta-analysis with a cross sectional design. a total of six research articles (full text) published online in 2015-2020, using the meta-analysis calculator program Review Manager 5.4. The main results of the study were the age of mothers 20-35 years during pregnancy (85.4%), low education level of junior high school, not working parity of mothers with children > 1 (65.7%), and most of the number of children with no more than two children. (68.1%), most of the mother's birth spacing does not exist, and mother's knowledge is good. The conclusion from the six articles was that three articles were analyzed in the meta-analysis, namely maternal education p = 0.002 OR = 3.2, mother's occupation p = 0.002 OR = 2.70, and mother's knowledge p = 0.0001 OR = 4.98. That data mean that there was a relationship between significantly with the nutritional status of under-fives in Indonesia. Variables of mother's age, mother's parity, number of mother's children, and mother's birth spacing cannot be analyzed in the meta-analysis.Keywords: Characteristics of mothers, nutritional status, children under five